Relationship Seekers Versus Relationship Selectors: Influence of Residential Mobility on How to Evaluate Others - Fang, Yuchen; Nunoi, Masato; Komiya, Asuka (Frontiers in Psychology, 2022)
The present study examined the effect of residential mobility on impression formation. In the study, participants were first engaged in a residential-mobility priming task where they were asked to imagine and describe either frequent moving life (high-mobility condition) or less frequent moving life (low-mobility condition). They then evaluated their attitudes towards four types of target persons: competent vs. incompetent and warm vs. cold. As a result, in the high-mobility condition, the effect of competence was observed only when participants evaluated a warm person, whereas in the low-mobility condition, it appeared only when participants evaluated a cold person. The potential influence of individual residential mobility on the relationship formation is also discussed.